International Development Aid in Decline: Implications for Nepal - Gwayali, Krishna (NCWA Annual Journal, 2026)
This article examines the evolving global development aid landscape and its implications for Nepal at a time when multilateral cooperation is increasingly constrained by geopolitical competition and shifting donor priorities. It argues that the apparent decline of traditional development aid reflects not its irrelevance, but the need for a fundamental redesign of the development cooperation architecture. Drawing on global trends, recent donor behavior, and Nepal’s aid experience, the paper advocates a transition toward greater country ownership, alignment with national systems, donor harmonization, and results orientation, complemented by stronger integration of trade, investment, and alternative financing instruments to support Nepal’s sustainable development trajectory. This article examines the evolving international development aid landscape through the lens of Nepal, analyses the drivers behind the apparent decline in traditional aid, and assesses its implications for Nepal’s development trajectory and policy choices.